Expression profiling of SCN8A and NDUFC2 genes in colorectal carcinoma - Igci, Y.Z.; Bozgeyik, E.; Borazan, E.; Pala, E.; Suner, A.; Ulasli, M.; Gurses, S.A.; Yumrutas, O.; Balik, A.A.; Igci, M. (Experimental Oncology, 2015)
The expression differences of SCN8A (which encodes type VIII alpha subunit of voltage gated sodium channel) and NDUFC2 (which encodes C2 subunit of Complex I enzyme in oxidative phosphorylation) genes were evaluated in paired colorectal cancer (CRC) tissues which was relied on our partial transcriptome analysis data in cancer cell lines. Materials and Methods: A total of 62 paired tissues of CRC patients (34 male, 28 female) were included in the study. The mRNA levels of SCN8A and NDUFC2 genes were determined by using real-time PCR (qRT-PCR and semiquantitative PCR). Results: SCN8A gene expression level was significantly lower in tumor tissues (p = 0.0128) and in the patients with the age below 45 years (p = 0.0049). There were also meaningful relationships between the gender, grade of CRC, tumor location, histopathological classification, and SCN8A expression. There was no NDUFC2 differential expression. However, the tumors taken from right colon had significantly lower NDUFC2 expression. Conclusion: Although the voltage gated sodium channels (VGSCs) and Complex I (CI) were associated to a number of diseases including different types of cancers, the different subunits of CI and individual members of VGSCs seem to be cancer type-specific in varying proportions. Key Words: colorectal carcinoma, SCN8A, NDUFC2, Complex I, voltage gated sodium channels, gene expression.